Modern Teaching Methods in the Algerian University and their role in building the knowledge society. Field study in the Universities of Guelma and Annaba (Sebha University Conference Proceedings, 2025)
This study aims to identify the extent to which modern teaching methods are used in the university teaching process at the Algerian University and their role in building the knowledge society, especially in the light of the rapid and successive developments and changes in the world today. This development is evident in the field of technology and knowledge, as well as its impact on the higher education sector and its components in the educational process, in particular teaching methods, because of their importance in the formation and preparation of efficient human resources. In this study, we have relied on the descriptive approach, as well as the form and interview as data collection tools. The results of the study show that usage degrees range from poor to moderate concerning modern teaching methods at the universities.